A Qualitative Assessment of Preventive Geriatric Care (American Journal of Physical Education and Health Science, 2024)
There was a projected growth of up to 80% between 1990 and 2025 in an older adult of Nigeria above 60 years of age. This projected growth assumes an increased workload for almost every healthcare provider to ensure optimal geriatric care. This study aimed to assess preventive geriatrics as a way of geriatric health care. Self-administered questionnaires were distributed among elderly people (60 years and above) residing in the Akure South Local Government Area for at least a year. The survey included several sections to assess multiple aspects such as sociodemographic information, assessment of primary preventive geriatrics, secondary preventive geriatrics as well as tertiary preventive geriatrics as methods of receiving geriatric health care. The response rate was around 96% of the respondents. The mean (± standard deviation) age of the cohort was 72.3 (±8.4) years. The primary (χ² =39.498, df = 12 p-value=0.000), secondary (χ² =58.5003, df = 12, p-value=0.000), and tertiary (χ² =35.8994, df = 12, p-value=0.000) preventive geriatrics were shown to be a way of geriatric health care. Geriatric health care should focus on prevention, medication use, personalized health management, fall prevention, and vaccination uptake. The study thus recommends that institutions in geriatric care provide educational programs, gratuitous medical evaluations, and social support strategies that can reduce the burden of preventive geriatric care for Nigerian elderly.